Ulinastatin alleviates cerebral ischemia-reperfusion injury in rats by activating the Nrf-2/HO-1 signaling pathway - Cui, Lei (Ann Transl Med, 2020)
BACKGROUND: Ulinastatin, a urinary trypsin inhibitor, is one of the widely used auxiliary drugs in the rescue of acute circulatory failure. This study aims to explore the protective mechanisms of ulinastatin on cerebral ischemia-reperfusion (I/R) injury. METHODS: A cerebral MCAO was established with middle cerebral artery occlusion (MCAO) in Sprague Dawley (SD) rats. Western blotting was employed to show protein expression. Oxidative stress markers [reactive oxygen species (ROS), superoxide dismutase (SOD), malondialdehyde (MDA), and glutathione (GSH)] and inflammatory cytokines (IL-6, IL-1β, and IL-18) were analyzed to show oxidative stress and inflammation. Hematoxylin and eosin (HE) and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) and triphenyltetrazolium chloride (TTC) staining were applied to show brain injury. RESULTS: HE, TUNEL and TTC staining indicated that ulinastatin significantly ameliorated cerebral I/R injury and reduced apoptotic cells in the MCAO brain tissue. Ulinastatin also reduced the MCAO-induced expression of intercellular adhesion molecule 1(ICAM-1)/caspase-3. Additionally, the highly expressed ROS, MDA and inflammatory cytokines (IL-6, IL-1β and IL-18) were significantly suppressed, and the inhibited SOD and GSH were recovered with ulinastatin treatment. Consequently, the expression of nuclear factor erythroid-2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) (which was significantly inhibited by MCAO) was re-activated by ulinastatin and/or TBHQ (an Nrf-2 activator), and treatment with ML-385 (an Nrf-2 inhibitor) blocked the inhibition of apoptosis, inflammation, and oxidative stress by ulinastatin. Our results indicate that the Nrf-2/HO-1 signaling pathway may be involved in the pharmacological mechanism of ulinastatin in cerebral I/R injury. CONCLUSIONS: Ulinastatin protected against inflammation and oxidative stress in cerebral I/R injuries via activation of the Nrf-2/HO-1 signaling pathway.